Manajemen Kualitas Pelayanan Nilai Dan Loyalitas Pelanggan : Suatu Kajian Literatur - Edi Irawan (Journal Economic Excellence Ibnu Sina, 2023)
This article aims to review and attempt to inform about the concept of service quality management, value and customer loyalty. The research method used is qualitative and literature studies or library research. Based on the results of the discussion above, it can be concluded theoretically that to understand value service quality management and customer loyalty management requires several important things, namely a). For service quality management the values that need to be considered are: Tangible, Reliability, Responsiveness, Assurance and Empathy, b). For loyalty management that needs to be considered, namely: Becoming a regular customer, Buying between product lines, Referring to others and Commitment to the company.